Fantastic Four. Vol. 4, Fortune favors the Fantastic - North, Ryan, 1980- (Marvel Comics, 2024)
"The Fantastic Four join the Blood Hunt and face down the vampires sinking their teeth into the Marvel Universe! But for all the FF's powers, can Mister Fantastic's scientific abilities do any good against the dark mysticism of their unliving foes?" --